Comparative Studies between Porous Silicon and Porous P-Type Gallium Nitride Prepared Using Alternating Current Photo-Assisted Electrochemical Etching Technique. (May 2020) - Sohimee, S. N.; Hassan, Z.; Ahmed, Naser M.; Radzali, R.; Quah, H. J.; Lim, W. F.
Abstract: Porous n-type Si and porous p-type GaN nanostructures were fabricated using alternating current photo-assisted electrochemical (ACPEC) etching in 1:4 volume ratio of hydrofluoric acid (HF) and ethanol (C2H5OH) for a duration of 30 min. The proposed approach to this work was to study pore formation on the Si and p-GaN substrates in the aspects of morphological and structural changes. The morphological and structural properties of porous Si and porous p-type GaN samples have been studied using field emission scanning electron microscopy (FESEM) measurement, energy-dispersive X-ray spectroscopy (EDX), atomic force microscopy (AFM), and high-resolution X-ray diffraction (HR-XRD) in comparison to the respective as-grown sample. FESEM analysis revealed that uniform pore size with triangular-like shape was formed in porous Si sample while circular-like shape pores were formed in the porous p-type GaN sample. AFM measurement revealed that the root-mean-square surface roughness of porous Si and porous p-type GaN was 6.15 nm and 5.90 nm, respectively. Detailed investigation will be presented in this work to show that ACPEC etching technique is a viable technique to produce porous nanostructures in different substrates.